The healing community: the importance of community-based interventions - Rooze, Magda; De Ruyter, Ariëlle; Ajduković, Dean; Fundter, Nienke; Hövels, Jorn (2006)
Community-based psychosocial interventions serve to meet a range of needs of a population affected either by a disaster (such as tsunami) or war. Experiences of care for the victims of tsunami, including the traumatized survivors and their families are described in three stages. The role of on-the-spot assistance, as well as the role of remembrance events, information and referral centre and information dissemination in the later stage is discussed. The range of community-based psychosocial interventions that have been tested in practice is areas affected by war are listed.
Projekt MZOS
ENG